Changes in seed quality of maize (KSC.704 hybrid) on the mother plant in different fertilizer, biochar and Trichoderma fungus treatments - mehdi ahmadyousefi; Behnam Kamkar; Javid Gherekhloo (علوم و فناوری بذر ایران, 2019)
This experiment was conducted as split – plot factorial based on randomized complete block design with three replications to determine the changes in maize’s seed quality on the parent plant at Jiroft's Nemooneh Field in 1395. The main factor was four levels of fertilizers (NPK) respectively representing the control, 30%, 70%, and 100% of recommended value) and biochar (respectively representing no biochar and biochar application), and two strains of Trichoderma (respectively representing Trichoderma atroviride and Trichodema harzianum) were assigned to sub plot. To assess the quality of maize seed (SC.704 hybrid) produced on the parent plant, seed vigor tests (cold test and accelerated ageing test) and germination test (normal seedling percentage, germination rate, seedling length and weight) were performed. The results showed that utilization of biochar, Trichoderma strains and fertilizer levels significantly affected normal seedling percentage, germination rate, and seedling length dry weight in standard germination, cold and accelerated ageing tests. The highest seed quality based on standard germination, cold and accelerated ageing tests was obtained via application of biochar, fungi Trichoderma (Trichodema harzianum) and 70% of the amount of fertilizer recommended for the region. According to the results obtained from standard germination and seed vigor tests (cold and accelerated ageing tests), using biochar, different fertilizer levels and fungus type leads to enhanced quality of seeds produced on maternal plant in comparison to control.